Desain dan Analisis Tegangan Double Crane Hook Kapasitas 5 Ton Menggunakan Metode Elemen Hingga - Jaya Asmara, Andra; Nadiansyah, Irham; Joan Magmadian, Alfred; Agus Dhombo, Armin; Harsoyo Sraun, Samuel; Prasetiyo, Angger Bagus (ReTII, 2023)
One of the industrial components used in the transportation of goods is a crane. A combination lifting mechanism consisting of lifting components whose main function can be used to lift, move and place one or more objects. More specifically, when crane hooks connected by chains or ropes are used, loads such as boxes, builders and suspended machinery or tools are transported, which are unloaded by chains wound through a pulley system with two drums, so crane hooks play a very important role. Utilising CAD software for modelling the double crane hook, the finite element approach is then used for meshing and structural analysis. Mild steel is the material, and the load is 2000N. The simulation produced a total displacement value of 0.1101 mm, a von Mises stress maximum value of 203.7 MPa, and a von Mises stress minimum value of 9.64e-04 MPa. The value of the corresponding strain ranges from 5.238e-09mm to 0.001216mm. 1.016 is the safety factor value. This indicates that a design's safety value is lower than its necessary value.